2021
DOI: 10.1038/s41467-021-25186-2
|View full text |Cite
|
Sign up to set email alerts
|

Amnion signals are essential for mesoderm formation in primates

Abstract: Embryonic development is largely conserved among mammals. However, certain genes show divergent functions. By generating a transcriptional atlas containing >30,000 cells from post-implantation non-human primate embryos, we uncover that ISL1, a gene with a well-established role in cardiogenesis, controls a gene regulatory network in primate amnion. CRISPR/Cas9-targeting of ISL1 results in non-human primate embryos which do not yield viable offspring, demonstrating that ISL1 is critically required in primate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
93
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(138 citation statements)
references
References 64 publications
12
93
0
Order By: Relevance
“…Indeed, a comparison of PGCLC-precursor cells in high and low PGC-competence cell lines (Chen et al ., 2019) revealed NODAL to be differentially expressed, consistent with a recently observed role for NODAL in PGCLC specification (Jo et al ., 2021). Slightly later, at 24h, an AMLC branch also became evident, expressing TFAP2A and, at later time points, ISL1 , a LIM/homeodomain transcription factor protein recently identified as an amnion marker (Guo et al ., 2020; Yang et al ., 2021) (Supplementary Fig. 2c-d).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a comparison of PGCLC-precursor cells in high and low PGC-competence cell lines (Chen et al ., 2019) revealed NODAL to be differentially expressed, consistent with a recently observed role for NODAL in PGCLC specification (Jo et al ., 2021). Slightly later, at 24h, an AMLC branch also became evident, expressing TFAP2A and, at later time points, ISL1 , a LIM/homeodomain transcription factor protein recently identified as an amnion marker (Guo et al ., 2020; Yang et al ., 2021) (Supplementary Fig. 2c-d).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, most of the genes whose expression was upregulated in the amnion-like cells were also induced in the AP-treated cells (Figures 4F, S4C, and S4D). They included genes such as ISL1 and HAND1, which have been reported to express in the primate amnion (Kno ¨fler et al, 2002;Ma et al, 2019;Yang et al, 2021). Immunostaining showed that the majority of cells expressed these proteins at this time point (Figures 4G and 4H).…”
Section: Amniotic Features At the Early Phase Of Differentiationmentioning
confidence: 77%
“…The BMP4-expressing cells are key for determining the fate of GATA3 + ExE cells. We supposed that these cells are analogous to the amniotic ectoderm, the EPI-derived epithelium that underlies the trophoblast layer to form an amniotic cavity in peri-implantation primate embryos, since BMP4 mRNA was detected in this extraembryonic tissue (Sasaki et al, 2016;Ma et al, 2019;Xiang et al, 2020;Yang et al, 2021). It was also reported that BAP induces amnion rather than trophoblast fate in human primed ESCs (Guo et al, 2021;Io et al, 2021).…”
Section: Amniotic Features At the Early Phase Of Differentiationmentioning
confidence: 98%
“…Furthermore, signaling from the amnion is required for mesoderm formation in non-human primates ( Yang, 2021 ). Therefore, in the hESC-hAEC condition, the cells would acquire a greater competence to derivate hPGC through non-embryonic mesoderm (they do not express some essential genes for establishing the primitive streak ) or an intermediate substate that generates both amnion and germline.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that primordial germ cells (PGCs) specified from the nascent amnion in the cynomolgus monkey ( Sasaki et al, 2016 ), although a recent study indicates that progenitors of human PGCs present a gene expression signature of both amniotic and gastrulation lineages ( Chen et al, 2019 ). In addition, the extraembryonic mesoderm is also closely related to the amnion ( Yang, 2021 ). These results indicate that the amnion has a predominant role in developing extraembryonic lineages such as trophoectoderm, extraembryonic mesoderm, and germline specification.…”
Section: Discussionmentioning
confidence: 99%